A METHODICAL AND TECHNOLOGICAL APPROACH TO INCREASE THE EFFECTIVENESS OF TEACHING 7TH GRADE EDUCATION IN A GENERAL SECONDARY SCHOOL - Abdupattaev Hasanboy Abdurahmonovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article deals with the issue of interpretation of the world (being) essence in the national education of the Uzbek people. It analyzes the scientific-philosophical, religious views, approaches and doctrines put forward by our ancestors in the interpretation of the essence of the world (being) from a scientific and pedagogical point of view.